Approximating of functions from Holder classes H- [0, 1] by Haar wavelets - Ahmedov A.A.; Abdul Sathar M.H.; Nurullah Rasedee A.F.; Binti Mokhtar N.F. (Institute of Physics Publishing, 2024)
Indexed by WOS/ Scopus